“Innovative financing and government guarantee in advancing sustainable development goals in water sector: A systematic literature review” - Hermawan, Hermawan; Afiah, Nunuy Nur; Fitrijanti, Tettet; Hermawan, Armand (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the role of innovative financing mechanisms, particularly government guarantees, in advancing the Sustainable Development Goals (SDGs) within the water sector through public–private partnerships (PPPs). Amid increasing water scarcity, aging infrastructure, and constrained public budgets, PPPs are increasingly recognized as vital instruments to mobilize private investment and enhance water service delivery. Employing a systematic literature review and bibliometric analysis using the Scopus database, the study analyzed 126 peer-reviewed journal articles through co-occurrence network analysis, thematic mapping, and citation analysis via the Bibliometrix R package. The findings reveal that government guarantees are essential in mitigating financial, political, and operational risks, thereby improving project bankability and investor confidence, particularly in developing economies. Case studies from Indonesia and China highlight the dual nature of such guarantees, which can enhance infrastructure viability when well-calibrated but also pose risks such as moral hazard and fiscal burden when poorly designed. The study concludes that strategically implemented guarantees can serve as effective policy tools to de-risk water sector investments and support the achievement of SDG 6 (Clean Water and Sanitation) and SDG 11 (Sustainable Cities and Communities). Practically, this research provides actionable insights for policymakers and stakeholders, emphasizing the need for transparent, fiscally responsible, and context-sensitive guarantee frameworks to ensure resilient, inclusive, and sustainable water infrastructure development.